The World Health Organization Access, Watch, and Reserve classification of antibiotics: an awareness survey among pharmacy professionals in a sub-Saharan country, Zambia - Steward Mudenda; McDonald David Wataya; Webrod Mufwambi; Joseph Yamweka Chizimu (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract